Transformations and representations supporting spatial perspective taking. Issue 4 (2nd October 2017) - Yu, Alfred B.; Zacks, Jeffrey M.
ABSTRACT: Spatial perspective taking is the ability to reason about spatial relations relative to another's viewpoint. Here, we propose a mechanistic hypothesis that relates mental representations of one's viewpoint to the transformations used for spatial perspective taking. We test this hypothesis using a novel behavioral paradigm that assays patterns of response time and variation in those patterns across people. The results support the hypothesis that people maintain a schematic representation of the space around their body, update that representation to take another's perspective, and thereby to reason about the space around their body. This is a powerful computational mechanism that can support imitation, coordination of behavior, and observational learning.